The Effects of Secondary Hyperparathyroidism on Circadian Blood Pressure in Hemodialysis Patients - Yakar, Burkay; Onalan, Erhan; Pirincci, Edibe; Kaya, Mehmet Onur; Demir, Mustafa (Coll Physicians & Surgeons Pakistan, 2021)
Objective: To determine the relationship between secondary hyperparathyroidism (sHPT) and circadian blood pressure (BP) rthym among patients undergoing hemodialysis treatment. Study Design: A descriptive and prospective cohort study. Place and Duration of Study: Department of Nephrology, Firat University Hospital, Turkey, between June and December 2019. Methodology: Eighty-five patients, undergoing hemodialysis three times a week, were included. The BP parameters and circa-dian blood pressure rhythm were measured by the mobil-o-graph sphygmomanometer. Non-dipper blood pressure phenomenon was defined as a night-time mean artery pressure (MAP) decrease of <10% from the daytime MAP; sHPT was defined parathormone >300 pg/ml. Results: Of the 85 participants, mean age was 57.07 +/- 14.46 years. In cohort, sHPT rate 58.8% (n =50) and non-dipper blood pressure pattern rate was 64.7% (n = 55). Systolic blood pressure (p=0.001), diastolic blood pressure (p=0.001), and mean arterial blood pressure (p<0.001) were higher in participants with sHPT. sHPT (p = 0.003) was an independent risk factor for non-dipper blood pressure pattern (odds ratio [OR] 0.065, 95% CI: 0.11-0.390). A negative correlation was identified between parathormone and the reduction in night blood pressure (r =-0.346, p=0.001). Conclusion: Secondary hyperparathyroidism can cause non-dipper blood pressure pattern by reducing the reduction in night blood pressure. Treatment of sHPT is important in the control of blood pressure and normal circadian blood pressure rhythm in tertiary protection in hemodialysis patients.
Keywords: Blood pressure; Circadian rhythm; Hyperparathyroidism secondary; Hemodialysis; Chronic kidney diseases